Immune-keratinocyte crosstalk in healthy and cancerous epidermis. Issue 19 (February 2021) - McCarthy, Shannon; Agudo, Judith
Abstract : The skin houses a vibrant ecosystem of immune cells, which are crucial for protecting the organism. However, recent years have also uncovered a close relationship between these skin immune cells and keratinocytes. Crosstalk between these populations has been shown to regulate various areas including stem cell division as well as which immune cells enter the healthy skin. Further, recent studies have also highlighted the skin immune system's involvement in cancerous settings. These insights have meaningful implications for the treatment of skin cancers as novel therapies increasingly leverage the immune system.